Detection of Asymptomatic Cases of Covid-19 Pregnant Women: A Systematic Review - Prima Soultoni Akbar; Santy Irene Putri; Astri Yunita (Universitas STRADA Indonesia, 2022)
Background: There have been many cases of the Covid-19 coronavirus detected in pregnant women. Data posted by the Centers for Disease Control and Prevention (CDC) shows that around 55% of pregnant women who are confirmed Covid-19 and hospitalized are asymptomatic. Purpose: The purpose of this study is to systematically review the detection of asymptomatic Covid-19 cases in pregnant women. The articles were selected from WorldCat, ProQuest, EBSCO, and PubMed Database journals published from January to April 2020.